Exploring the Effectiveness of Project-Based Blended Learning in Science E-Books for Improving Digital Literacy - Ramdhani Sucilestari; Kurniawan Arizona; Baiq Mutiara Alika Nirmala; Aulial Aspia; Masiah (Postgraduate, University of Mataram, 2025)
This study addresses the pressing need to enhance digital literacy among students, particularly within the framework of project-based learning that incorporates e-books in the science curriculum. The primary aim is to assess the effectiveness of the Project-Based Blended Learning (PBBL) approach in boosting students' digital literacy. A quasi-experimental design was employed, with pre-test and post-test assessments conducted on two student groups. The experimental group engaged in project-based learning using e-books, while the control group followed traditional teaching methods. Data analysis, performed through t-tests, was used to compare the digital literacy improvements between the groups. The findings revealed that students who participated in PBBL with e-books showed a substantial increase in digital literacy compared to those in conventional learning environments. E-books in project-based learning offer greater flexibility, interactivity, and dynamism, significantly fostering the development of digital literacy skills. This research contributes empirical evidence supporting the effectiveness of PBBL in enhancing digital literacy and offers valuable insights for advancing technology-driven teaching approaches in science education.